Two new species of Mycovellosiella - R.K. SINGH, R.N. KHARWAR* and (Indian Phytopathology, 2003)
Two species of Mycovellosiella viz., M. aegli sp. novo on Aegle marme/os (Rutaceae), and M. terminalae sp. novo on Terminalia arjuna (Combritaceae), collected from forest flora of Uttar Pradesh are described, illustrated and compared with allied taxa.